PENGARUH CSR DAN KONTEN MARKETING TERHADAP CUSTOMER ENGAGEMENT BRAND WARDAH PADA PLATFORM TIKTOK DI KOTA SAMARINDA - Andi Nabilah Az-zahrah; Annisa Wahyuni Arsyad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) and content marketing on customer engagement for the Wardah brand on the TikTok platform, specifically in Samarinda City. The background of this research is based on the increasing competition in the cosmetics industry and changes in increasingly digital consumer behavior, requiring companies to optimize marketing strategies based on social values ​​and digital content. This study used a quantitative approach with a survey method of 150 respondents who were TikTok users, Wardah consumers, and had interacted with Wardah's CSR content and programs. The sampling technique used purposive sampling, with data collected through a Likert-scale questionnaire. Data analysis was performed using multiple linear regression with the help of SPSS. The results showed that CSR and content marketing, both partially and simultaneously, had a positive and significant effect on customer engagement. The content marketing variable had a more dominant influence than CSR, with a regression coefficient of 0.636, while CSR was 0.331. Simultaneously, the two variables were able to explain 84.5% of the variation in customer engagement. These findings indicate that a creative, relevant, and interactive content strategy on TikTok is a key factor in increasing consumer engagement, while CSR plays a crucial role in building trust and a positive brand image. Therefore, companies are advised to integrate CSR programs with content marketing strategies to sustainably increase customer engagement.